2018
DOI: 10.3892/ol.2018.8540
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA ZNF674‑1 acts as a cancer suppressor in nasopharyngeal carcinoma

Abstract: Abstract. Nasopharyngeal carcinoma (NPC) is the most frequently occurring carcinoma of the head and neck. The complexity of NPC makes it difficult for it to be diagnosed and treated at an early stage. Certain long non-coding RNAs (lncRNAs) are closely associated with the carcinogenesis of NPC. In the present study, the expression of lncRNA ZNF674-1 in NPC tissues and an NPC cell line was analyzed and was revealed to be downregulated compared with normal tissues and cells. When the expression of lncRNA ZNF674-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…As miRNA sponges to play roles, lncRNAs are proven to regulate tumorigenesis [ 19 ]. We determined the localization of LINC00210 in NPC cells and found that it mainly located in the cytoplasm ( Figure 3 A), suggesting LINC00210 might be a miRNA sponge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As miRNA sponges to play roles, lncRNAs are proven to regulate tumorigenesis [ 19 ]. We determined the localization of LINC00210 in NPC cells and found that it mainly located in the cytoplasm ( Figure 3 A), suggesting LINC00210 might be a miRNA sponge.…”
Section: Resultsmentioning
confidence: 99%
“…In NPC, a few of lncRNAs have been identified as indicators for patients’ prognosis. For instance, Nie et al [ 19 ] showed that lncRNA ZNF674-1 down-regulation predicts poor prognosis in NPC. Wu et al [ 25 ] showed that lncRNA ANRIL is up-regulated by SOX2 and promotes the growth of NPC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that long noncoding RNAs (lncRNAs) are generally longer than 200 nucleotides and have no ability to be translated into proteins. 5 Extensive investigations have proven that lncRNAs are implicated in a variety of cellular processes, such as cell proliferation, cell cycle, cell metastasis, and cell apoptosis. 6 LncRNA n326322 promotes the proliferation and invasion in NPC.…”
Section: Introductionmentioning
confidence: 99%
“…A vast number of lncRNAs are aberrantly expressed in NPC. For instance, NEAT1,12 DANCR,13 and HOTTIP14 are overexpressed in NPC and function as oncogenes, whereas ZNF674-1,15 LET,16 and LINC008617 are underexpressed in NPC and exert tumor-suppressive actions. Therefore, lncRNAs may represent useful therapeutic targets in NPC.…”
Section: Introductionmentioning
confidence: 99%